Devotion in honor of St. Dymphna, virgin and martyr, patroness of those afflicted with nervous disorders : brief history of her life. (Cincinnati : Catholic Chaplain, Longview Hospital, 1951)
Catholic pamphlet. Devotional work.
Includes a litany, novena, and brief account of the saint's life and miracles.
Mode of access: Internet.
Keywords: Dympna, -- Saint; Dympna, -- Saint -- Prayers and devotions; Dympna, -- Saint; Sick; Sick -- Prayers and devotions; Novenas; Devotional literature; Prayers and devotions